SORGHUM GENOTYPES EVALUATION UNDER SALINITY LEVELS AND GAMMA RAY DOSES - TABOSA, JOSÉ N.; COLAÇO, WALDECIRO; REIS, ODEMAR V. DOS; SIMPLÍCIO, JOSIMAR B.; CARVALHO, HÉLIO W. L. DE; DIAS, FLAVIO M. (REVISTA BRASILEIRA DE MILHO E SORGO, 2010)
Experiments were carried out during the year of 2004 with the collaboration of the Nuclear Energy Department (DEN), the Federal University of the State of Pernambuco (UFPE), and the Agricultural Research Corporation of the State of Pernambuco (IPA). The main objective was to identify, evaluate and select high salinity resistance sorghum plants (from varieties V1- IPA 467-4-2, V2- IPA- 02-03-01 and V3- IPA- Sudan 4202) under ionizing radiation effects and electrical conductivity of the soil saturation extract – EC levels. The doses (applied to the seeds) of gamma rays from 60Co were 0, 450, 500 and 600 Gy and the salinity levels used were 0, 15 and 30 dS/m of electrical conductivity – CE. The main results were: a) electrical conductivity levels between 15 and 30dS/m and gamma ray doses of 450 Gy allowed for the selection of sorghum genotypes that are resistant to salinity; b) molecular markers of the microsatelites type SSR - simple sequences repeated, revealed genetic changes in appearance of irradiated and non irradiated sorghum genotypes.